Case Report on Integrative Management of Non- Healing Ulcer in A Diabetic Patient (Madhumegha Pun) - Radha Sudalaimani, Supriya Kanagaraj, Mekala Ayyakkannu, Nandhagopal Kannaiyan, Mariappan Andi, Bhanu Shaik, Samraj Karunanidhi (South Eastern European Journal of Public Health, 2025)
Diabetic foot ulcer (DFU)- Madhumega pun is a wound that affects individuals with uncontrolled diabetes and about 6% of these patients require hospitalization due to ulcer related complications. The underlying hyperglycemia gets intensified by ischaemia the microvascular complication of Diabetes mellitus resulting in nonhealing chronic ulcers and a high prevalence rate of amputation in diabetics. In this article a case study, of DFU managed with the integration of Siddha and allopathic treatments has been explained. Guidelines for diabetic foot ulcer management was followed along with incorporation of Siddha procedures like Thespesia populnea leaf decoction (TPLD) as kazhuvuneer, and Vanga Virana Kalimbu (VVK) and Palagarai parpam as topical application.The ulcer healed upto 80%. Since no previous clinical evaluation has been done this case study has been documented to explore its effectiveness in healing chronic ulcers. The prognosis was assessed at different time points using Leg Ulcer Measurement Tool (LUMT).